2015
DOI: 10.1111/bph.13122
|View full text |Cite
|
Sign up to set email alerts
|

Role of aldehyde dehydrogenase in hypoxic vasodilator effects of nitrite in rats and humans

Abstract: Background and PurposeHypoxic conditions favour the reduction of nitrite to nitric oxide (NO) to elicit vasodilatation, but the mechanism(s) responsible for bioconversion remains ill defined. In the present study, we assess the role of aldehyde dehydrogenase 2 (ALDH2) in nitrite bioactivation under normoxia and hypoxia in the rat and human vasculature.Experimental ApproachThe role of ALDH2 in vascular responses to nitrite was studied using rat thoracic aorta and gluteal subcutaneous fat resistance vessels from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 38 publications
0
17
1
Order By: Relevance
“…Cyanamide, an ALDH inhibitor, only slightly attenuated the nitrite effect. Recently Arif and colleagues reported, both in human resistance vessels and in rat aorta, that nitrite-mediated vasodilatation during hypoxia involved ALDH2 [11]. A possible explanation for the different conclusion in our study may be related to different characteristics of the renal vasculature.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Cyanamide, an ALDH inhibitor, only slightly attenuated the nitrite effect. Recently Arif and colleagues reported, both in human resistance vessels and in rat aorta, that nitrite-mediated vasodilatation during hypoxia involved ALDH2 [11]. A possible explanation for the different conclusion in our study may be related to different characteristics of the renal vasculature.…”
Section: Discussioncontrasting
confidence: 69%
“…Administration of inorganic nitrate or nitrite to humans and rodents is linked to enhanced NO-like bioactivity such as vasodilatation, increased blood flow, reduction in blood pressure, and generation of cGMP [2][3][4][5]. A handful of enzymatic and nonenzymatic pathways have been demonstrated to catalyze nitrite reduction to NO in blood and tissues, including deoxyhemoglobin and deoxymyoglobin [6,7], aldehyde oxidase (AO) [8], aldehyde dehydrogenase (ALDH) [9][10][11], xanthine oxidoreductase (XOR) [12,13], and endothelial NO synthase (NOS) [14]. Nitrite has enhanced bioactivity at low oxygen tensions and under acidic conditions [6,15,16], and studies have demonstrated a protective effect of this anion in ischemia-reperfusion injury [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, for SE Asian subjects, consumption of nitrate had no effect on either DP or HR, suggesting no reduction in cardiac work following nitrate supplementation. What is unclear from our data is whether these observations represent a direct effect of the nitrate or whether the nitrate required biotransformation to an active species in order to demonstrate vascular activity …”
Section: Discussionmentioning
confidence: 85%
“…Commensal bacteria reduce dietary nitrate to nitrite in the buccal cavity. This nitrite then undergoes further reduction to NO through the actions of aldehyde dehydrogenase 2 (ALDH2) . This mechanism is given further support as ALDH2 transcript was found within the intimal layer of blood vessels close to the site of NO activity.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation